Inertial projection and contraction algorithms for variational inequalities - Dong, Q. L.; Cho, Y. J.; Zhong, L. L.; Rassias, Th. M. (Journal of global optimization, 2018)
In this article, we introduce an inertial projection and contraction algorithm by combining inertial type algorithms with the projection and contraction algorithm for solving a variational inequality in a Hilbert space H . In addition, we propose a modified version of our algorithm to find a common element of the set of solutions of a variational inequality and the set of fixed points of a nonexpansive mapping in H . We establish weak convergence theorems for both proposed algorithms. Finally, we give the numerical experiments to show the efficiency and advantage of the inertial projection and contraction algorithm.